2017
DOI: 10.37358/rc.17.11.5925
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Technology for the Detection of Antimicrobial Resistance Genes Present in Hospital and Community Acquired Methicillin Resistant S.aureus Strains

Abstract: Antimicrobial resistance (AMR) represents a real burden for the modern medicine. One of the most frecvently isolated hospital acquired (HA) pathogens wordlwide, is Methicillin resistant Staphylococcus aureus (MRSA). Recently not only HA, but also community-acquired MRSA (CA-MRSA) infections have been reported. A prospective study was performed between February 2009 and October 2010, with the aim to investigate bacterial resistance of CA-MRSA and HA-MRSA. DNA microarray technology has been used for the detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In the Gram-positive group, a higher degree of resistance of MRSA was found to be against penicillin (95.37%), erythromycin (79.62%), clindamycin (78.70%), tetracycline (70.37%) and ciprofloxacin (65.74%), consistent with other findings [1,10]. A prospective study performed in Romania by Licker at al, identified 66.51% MDR and 20.18% XDR S.aureus strains [24], in the conditions in which MRSA has been the most important cause of antimicrobial-resistant healthcare-associated infections worldwide, with higher percentages in the southern and south-eastern parts of Europe [15]. The most active antibiotic against MRSA (table 5) was linezolid, with almost all strains (105) being susceptible (table 5).…”
Section: Resultssupporting
confidence: 82%
“…In the Gram-positive group, a higher degree of resistance of MRSA was found to be against penicillin (95.37%), erythromycin (79.62%), clindamycin (78.70%), tetracycline (70.37%) and ciprofloxacin (65.74%), consistent with other findings [1,10]. A prospective study performed in Romania by Licker at al, identified 66.51% MDR and 20.18% XDR S.aureus strains [24], in the conditions in which MRSA has been the most important cause of antimicrobial-resistant healthcare-associated infections worldwide, with higher percentages in the southern and south-eastern parts of Europe [15]. The most active antibiotic against MRSA (table 5) was linezolid, with almost all strains (105) being susceptible (table 5).…”
Section: Resultssupporting
confidence: 82%
“…Most patients enrolled in this study received antibiotic therapy prior to various surgeries. It was found that antibiotic prophylaxis was not effective against the isolated pathogenic strains, particularly MRSA, enterococcus and Gram-negative bacillus species, additional prophylactic measures being necessary [5].…”
Section: Resultsmentioning
confidence: 99%
“…In other studies conducted with the aim of highlighting the MDR strains which caused other types of infections besides BSI, Klebsiella ranks first among isolated microorganisms, 12 , 14 , 15 with the same findings in other researchers’ studies. 16 …”
Section: Discussionmentioning
confidence: 99%